OPPORTUNITIES AND CHALLENGES IN IMPLEMENTING CO-CURRICULAR ACTIVITIES PERCEIVED BY TEACHERS AS FACILITATORS AT STATE VOCATIONAL SCHOOL 1 JAMBI CITY: A NARRATIVE INQUIRY - Putimasurai; Nazurty; Anggraini, Desti; Aniswaty, Maida (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2023)
This study aims to give a general overview of the opportunities and difficulties the facilitators encountered at State Vocational School 1 Jambi City when implementing co-curricular activities. Using in-depth interviews and narrative inquiry as the research methodology, two English teachers who have been practicing P5 for two years were designated as the Facilitators. According to the findings, offering the P5 as a co-curricular has the ability to strengthen the school program, offer a more concentrated character development program, foster teacher collaboration, and raise student performance in terms of independence and creativity. One of the issues encountered during P5 implementation is locating references for P5 activity design and administration.